If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=-2-5y+7y-2(4y-7)
We simplify the equation to the form, which is simple to understand
y=-2-5y+7y-2(4y-7)
Reorder the terms in parentheses
y=-2-5y+7y+(-8y+14)
Remove unnecessary parentheses
+y=-2-5y+7y-8y+14
We move all terms containing y to the left and all other terms to the right.
+1y+5y-7y+8y=-2+14
We simplify left and right side of the equation.
+7y=+12
We divide both sides of the equation by 7 to get y.
y=1.71428571429
| 1+3n=6n+4 | | 1/2+3/4z=-5/2 | | 15-12x=2x+13 | | 9x-4=7x-1 | | 9x-4+7x-1= | | E=ex | | k^2+4k+4=-7 | | 5(a-4)=6(a-7) | | -[8x+(3x+8)]=1-(3x+3) | | -0.64-6.7u=-6.7u | | 8-3[5-(4y-8)]=0 | | -13+2r+2-r=1+4r | | x^5+3x^4-3x^3-x^2-3x+3=0 | | 17p-1=3p+12+14p | | 10a-45=3(a-15) | | x+92=-47 | | -4(1-4v)-6=-32+5v | | -2+4z=4z-2 | | 10a-45=3a-45 | | 2r+1=4r-1 | | x-3=-40 | | 8(c-3)=5c+24 | | 79+x=94 | | 3x-4(2x-9)=5x+11 | | w=100/4 | | -19.55-6.6j=-19.3j+17.1j+18.73 | | (-51)+x=38 | | 6x+4x=18 | | 8h-11(h+4)=-77 | | 7x+4x=-x | | 1108473/4=x | | 7(z+11)=4(z+11) |